Metaichmiakó (for EMS Synthi100) - Koutsomichalis, Marinos (My University, 2026)
Metaichmiakó is the first work composed for KSYME-CMRC’s EMS Synthi100 following its restoration and on the occasion of Documenta14 in Athens. The instrument (made in 1963) had been out of order since the early ’80s and was restored by Daniel Araya and Jari Suominen under my supervision. The work was performed at Athens Concert Hall (Megaron). https://www.documenta14.de/en/artists/16209/ksyme-cmrc